IMPLEMENTASI KEBIJAKAN JABATAN FUNGSIONAL ANALIS PRASARANA DAN SARANA PERTANIAN DI DIREKTORAT PESTISIDA KEMENTERIAN PERTANIAN - Astuti Kusuma Wardhani (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the implementation of the Functional Position Policy for Agricultural Infrastructure and Facilities Analysts (Analis PSP) at the Directorate of Pesticides, Ministry of Agriculture. The study employed a qualitative approach using Larry N. Gerston’s policy implementation theory consisting of translation ability, resources, limited number of players, and accountability dimensions. Data were collected through in-depth interviews, observations, and documentation studies involving informants from the Directorate General of Agricultural Infrastructure and Facilities. The findings indicate that the implementation of the Functional Position Policy for Agricultural Infrastructure and Facilities Analysts has not been fully optimal. Several challenges were identified, including limited human resources, insufficient technical training, weak understanding of policy implementation, imbalance in workload distribution, and lack of performance-based accountability mechanisms. In addition, the utilization of information technology in managing agricultural infrastructure and facilities remains limited. This study concludes that strengthening institutional capacity, competency development, and digital governance systems are necessary to improve the effectiveness of the implementation of the functional position policy in supporting agricultural modernization and national food security.